PENGARUH STRES KERJA, KOMPETENSI, INDEPENDENSI DAN PROFESIONALISME TERHADAP KUALITAS AUDIT PADA INSPEKTORAT PROVINSI BANTEN - Rohmanullah, Ido; Yazid, Helmi; Hanifah, Imam Abu (Pascasarjana Universitas Sultan Ageng Tirtayas, 2020)
AbstractThis study aims to examine the factors that affect audit quality. This research develops theoretical framework as the basic hypothesis, to answer the research questions consisting of: (1) how the influence of job stress on audit quality, (2) how the influence of competence on audit quality, (3) how influence of independence to audit quality, and (4) how the effect of professionalism on audit quality. The sample of this study is 81 people auditor Inspectorate of Banten Province. This research uses census method. Data are primary data collected through questionnaires. Data analysis method to test the hypothesis is Structural Equation Modeling (SEM) analysis using Partial Least Square (PLS). The results of this study indicate that Job stress affects audit quality, Competence has an effect on audit quality, Independence has an effect on audit quality, and (4) Professionalism has an effect on audit quality.